Design of quad band antenna for motorola transceiver system - Vijayasuriar, Rubini (2008)
A rapid growth of personal communication has lead to the need for more compact antennas. In addition, the increase in the capacity and quality of the new services provided by mobile communications requires the development of new antennas with wider bandwidths. At the same time, due to miniaturization of the transceivers, the antennas should have small dimensions; low profile and the antennas should have the possibility to be embedded in the terminals. This project involves the design of quadband antenna for a transceiver system of Motorola Penang. Available antennas are for specific application and there is an immediate need to enhance these for quad-band application. The operating frequencies of the antenna that will be looked into are the 800 Mhz/ 900Mhz, the GPS frequency of 1.5 GHz and 2.4GHz is WLAN s used for potential dual mode iDEN-WLAN product Transmission line technology will be employed. The operating frequencies will be controlled by different radiating structures of the proposed antenna. Specific geometrical ratio of the individual segregated segment will be applied. Hence, the frequency ratio of two adjacent resonant frequencies can be easily tuned to the desired value of the wireless application. Simulations will be performed on the designed antennas for good quad-band operation with low reflections. The work involves simulations using SEMCADX simulation tool. This simulation tool is a 3-D EM solver and is capable of representing data in time and in frequency domain. The results obtained was analyzed.